2016
DOI: 10.1128/jvi.00602-16
|View full text |Cite
|
Sign up to set email alerts
|

HSP90 Chaperoning in Addition to Phosphoprotein Required for Folding but Not for Supporting Enzymatic Activities of Measles and Nipah Virus L Polymerases

Abstract: Nonsegmented negative-stranded RNA viruses, or members of the order Mononegavirales, share a conserved gene order and the use of elaborate transcription and replication machinery made up of at least four molecular partners. These partners have coevolved with the acquisition of the permanent encapsidation of the entire genome by the nucleoprotein (N) and the use of this N-RNA complex as a template for the viral polymerase composed of the phosphoprotein (P) and the large enzymatic protein (L). Not only is P requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
82
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(90 citation statements)
references
References 73 publications
5
82
0
Order By: Relevance
“…We next analyzed whether the involvement of Hsp70 and CHIP in the maturation and degradation of the L protein was common among other paramyxoviruses. Consistent with a previous study (12), we found that the MeV L protein was also degraded by 17-AAG (Fig. 9A).…”
Section: Hsp90 Is Required For Muv Polymerase Formationsupporting
confidence: 82%
See 4 more Smart Citations
“…We next analyzed whether the involvement of Hsp70 and CHIP in the maturation and degradation of the L protein was common among other paramyxoviruses. Consistent with a previous study (12), we found that the MeV L protein was also degraded by 17-AAG (Fig. 9A).…”
Section: Hsp90 Is Required For Muv Polymerase Formationsupporting
confidence: 82%
“…The data showed that the amount of the L protein in the soluble fraction was increased when the L and P proteins were expressed together ( Fig. 4C and D), suggesting that the MuV P protein also functions as a chaperone for the MuV L protein, as shown for other paramyxoviruses (10)(11)(12). Therefore, both Hsp90 and the P protein contributed to the stability of the L protein.…”
mentioning
confidence: 75%
See 3 more Smart Citations